New species of Philopterus Nitzsch, 1818 (Ischnocera: Philopteridae), with notes on Cypseloecus Conci, 1941 - Gustafsson, Daniel R.; Najer, Tomas; Zou, Fasheng; Bush, Sarah E. (European Journal of Taxonomy, 2022)
We describe and illustrate eight new species of chewing lice in the genus Philopterus Nitzsch, 1818, parasitic on hosts in the bird families Cardinalidae, Chloropseidae, Hirundinidae, Icteridae, Motacillidae, Paridae, and Vangidae from China, Peru, South Africa, Thailand, and the USA. They are: Philopterus coriaceus sp. nov. from Molothrus oryzivorus oryzivorus (Gmelin, 1788); P. hebes sp. nov. from Chloropsis aurifrons inornata Kloss, 1918 and C. cochinchinensis kinneari Hall & Deignan, 1956; P. micropunctatus sp. nov. from Anthus hodgsoni Richmond, 1907; P. afropari sp. nov. from Melaniparus cinerascens cinerascens (Vieillot, 1818); P. pseudhirundo sp. nov. from Pseudhirundo griseopyga Sundevall, 1850; P. sinensis sp. nov. from Hemipus picatus capitalis (Horsfield, 1840); P. stansburyensis sp. nov. from Pheucticus melanocephalus melanocephalus (Swainson, 1827); and P. trepostephanus sp. nov. from Tephrodornis virgatus fretensis Robinson & Kloss, 1920 and T. v. mekongensis Meyer de Schauensee, 1946. Philopterus hebes sp. nov. constitutes the first record of the genus Philopterus from the Chloropseidae. We also provide some notes on the morphology and status of Cypseloecus Conci, 1941.